Network and Embedded Applications of Automatic Speech Recognition - Hataoka, Nobuo; Kokubo, Hiroaki; Lee, Akinobu; Kawahara, Tatsuya; Shikano, Kiyohiro (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2008)
ASR (Automatic Speech Recognition) is one of key technologies in the upcoming Ubiquitous Computing and Ambient Intelligence. In this paper, first, the surveys on processing devices such as microprocessors and memories, and on communication infrastructure, especially wireless communication infrastructure relating to ASR are reported. Second, the embedded version of CSR (Continuous Speech Recognition) software for the mobile environmental use of ASR is reported. As the devices, RISC based microprocessors, semiconductor memories, and HDD are summarized. For the communication infrastructure, mobile communications and wireless LANs are described. Finally, implementation results of the free CSR software called Julius on the T-engineTM consisting of an SH-4A mi-croprocessor are reported.